Endovascular management of iliac aneurysmal disease with hypogastric artery preservation - Schiro, Brian J.; Gandhi, Ripal T.; Peña, Constantino S.; Geronemus, Adam R.; Powell, Alex; Benenati, James F. (Cardiovascular Diagnosis and Therapy; Vol 8, Supplement 1 (April 13, 2018): Cardiovascular Diagnosis and Therapy (Advanced aortic imaging and intervention), 2017)
Common iliac artery aneurysms (CIAAs) pose a challenge in endovascular aneurysm repair. Aneurysm repair of CIAA traditionally requires embolization of the ipsilateral hypogastric artery (HA). Symptoms of buttock claudication and more feared complications of pelvic ischemia make HA preservation an appealing addition to aneurysm repair. In this review, we discuss various methods of CIAA repair with devices specifically designed for aneurysm repair and other custom techniques of HA preservation.